(untitled) (LEARNing Landscapes, 2015)
The development of "inquiry as stance" is a foundational component of the teacher research movement. Yet, it is difficult to exemplify this construct to gain insights into its meaning and what it might look like in practice. The purpose of this article is to initiate discussion about the construct of stance through the provision and analysis of an eight-minute video clip depicting one teacher researcher’s work. Three components of stance are discussed in relationship to the video example: (1) Data Collection as a Part of Teaching, (2) Roles of Inquirer and Teacher Blend Seamlessly With One Another, and (3) Commitment to the Creation of More Equitable Classrooms.